Ostensibly indirect narration in films and motion pictures - Marek Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
The article proposes the hypothesis that on the basis of analytical and interpretative practices, when describing, analysing and interpretating moving images, a dichotomous, binary division into objective and subjective images is a highly questionable move: it does not lend itself to an absolutely unequivocal resolution. In film, as in the field of moving images as a whole, there is no objective narration, just as there is no subjective narration. What emerges is an ostensibly dependent narration (or ostensibly independent), blending and merging both of these aspirations in diverse ways.